1975
DOI: 10.1073/pnas.72.11.4635
|View full text |Cite
|
Sign up to set email alerts
|

Relationship in nucleic acid sequences between mouse mammary tumor virus variants.

Abstract: Primary cultures of mouse mammary carcinomas were used as a source of both radioactively labeled and unlabeled 60 Variants of the mouse mammary tumor virus (MMTV) have been identified by different biological characteristics such as virulence, host range, mode of transmission, and histological type of tumor induced (1-5). Proviral sequences of MMTV have been reported (6) to be uniformly omnipresent in the cellular genome of mouse strains with high and low mammary tumor incidence, and to be expressed in all tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Numerous transgenic mouse models have been developed (Li et al, 2000;Stewart et al, 1984), many of them utilizing MMTV-LTR for targeting transgene expression to the mammary epithelium and allowing stimulation by lactogenic hormones. In reproductively separated feral mouse species (Callahan et al, 1982Escot et al, 1986;Gallahan et al, 1986;Imai, 1996;Imai et al, 1994,;Morris et al, 1977;Schlom et al, 1978) and Asian mouse populations Michalides and Schlom, 1975;Teramoto et al, 1980), tumor formation occurs in low percentages. In certain Asian mouse populations of Mus musculus, BC occurs with less than 1% of incidence, and with relatively long latency, after 18 months of age.…”
Section: Tumorigenesis In Micementioning
confidence: 95%
“…Numerous transgenic mouse models have been developed (Li et al, 2000;Stewart et al, 1984), many of them utilizing MMTV-LTR for targeting transgene expression to the mammary epithelium and allowing stimulation by lactogenic hormones. In reproductively separated feral mouse species (Callahan et al, 1982Escot et al, 1986;Gallahan et al, 1986;Imai, 1996;Imai et al, 1994,;Morris et al, 1977;Schlom et al, 1978) and Asian mouse populations Michalides and Schlom, 1975;Teramoto et al, 1980), tumor formation occurs in low percentages. In certain Asian mouse populations of Mus musculus, BC occurs with less than 1% of incidence, and with relatively long latency, after 18 months of age.…”
Section: Tumorigenesis In Micementioning
confidence: 95%
“…The data of Fig. 2 (a) showed that DMBA-LV vRNA was able to protect MMTV (C3H) by 90~, indicating that the MMTV present in DMBA-LV is more related to milk-borne MMTV than to endogenous MMTV [the latter being only 70 to 75 related to milk-borne MMTV (Michalides & Schlom, 1975;Ringold et al, 1976)]. From the 1/2 Crt value (3.0 x 10 -2) the type B nucleotide sequences can be calculated to be present in at least a tenfold excess over the type C sequences.…”
Section: Nucleotide Sequence Homology To Type B Retrovirusesmentioning
confidence: 99%
“…Most other inbred strains of mice have a low and variable incidence of mammary tumors which occur late in life. Yet, like the high-incidence strains, they carry in their germ line multiple copies of the MMTV proviral genome (3)(4)(5)(6). The extent to which the genetically transmitted MMTV proviral genomes are involved in the development of spontaneous mammary tumors in low-incidence mouse strains varies with the strain in question.…”
mentioning
confidence: 99%